THE ABSURD TEACHER - Stott, Laurence (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1980)
There is a presumption about the enterprise of education, that the generation that teaches knows where the generation that learns should go. This presumption swiftly reduces itself either to an instruction in imitation, of the teaching generation’s present state of organization and of mind - or to an exhortation to achieve some state of organization or of mind that ought to be. In this essay Stott elegantly contemplates Camus contemplating the unacceptability of either conviction - the first because of the purely accidentai reasons for any society’s current customs and beliefs, the second for want of any evidence as to a purpose in human existence. For him the ideal teacher is one who, recognising the futility in either rationale, accepts the absurdity of life and deals with it as it is. He hopes his children may find such a teacher. RÉSUMÉ D’aucuns prétendent à propos de l’éducation que la génération de ceux qui enseignent sait parfaitement vers quoi se dirige celle des enseignés. Cela revient à dire que l’enseignement n’est qu’une pâle imitation de l’organisation et de l’état d’esprit des maîtres de la génération précédente ou une exhortation lancée aux futurs enseignants pour qu’ils changent d’organisation ou d’état d’esprit. Dans cet essai, Stott examine Camus qui considère l’inadmissibilité des deux convictions, la première en raison du caractère purement fortuit des us, coutumes et croyances d’une société donnée, la deuxième à cause du manque de preuves quant au but de l’existence de l’être humain. Pour lui, le professeur idéal est quelqu’un qui, tout en admettant la futilité des deux raisonnements, accepte l’absurdité de l’existence et apprend à y faire face. Il espère que ses enfants tomberont sur ce genre d’enseignant.